Design of an atmospheric muon tomographer for material identification based on CORSIKA+ GEANT4 simulations - Rengifo, J.A.; Bazo Alba, J.L. (Elsevier, 2026)
In recent years, muon tomography has appeared as a powerful and innovative technique for non-invasive imaging of both large and small structures, with applications in different fields such as geology, archeology and security. This study presents the design and simulation of a portable, easy-to-construct detector based on plastic scintillators and silicon photomultipliers using current technology. The cosmic ray flux reaching the Earth's atmosphere was input to CORSIKA to simulate atmospheric muons and other secondary particles at ground level. The detector and the target object geometry and materials were simulated using GEANT4, transporting the previously generated muon flux. Two muon tomography methods, based on data on muon absorption or scattering, were employed to distinguish objects composed of different materials. Statistical differences were quantified for various object sizes and materials. Using a 3 $\sigma$ threshold in the first method, it was determined that objects made of lead can be distinguished from those made of other materials. The observation times required to differentiate an object made of lead from one made of aluminum were $1.3 \pm 0.2$ days and $9.4 \pm 3.7$ days for the first and second methods, respectively.
Keywords: Muon tomography; Cosmic rays; Scintillation detectors; https://purl.org/pe-repo/ocde/ford#1.03.03